Effectiveness of Organic Pesticides made from Cigarette Stub to the Attack Pest Intensity of Terminalia cattapa - Yudanto, Yusuf Arya; Primartu, Syaviela Viagul Sams; Fuadiyah, Dinana Anissatul; Arifan, Fahmi (Research Journal of Life Science, 2021)
The high consumption of cigarettes, especially in Indonesia, will produce harmful waste for the environment called cigarette stubs.  The waste of cigarette stubs reacts with any kinds of pathogenic fungus such as Fusarium oxysporum, Colletotrichum gloeosporiodes, Rigidoporus lignosus, and Sclerotium rolfsii. The usage of cigarette stubs as an alternative raw material for making organic pesticides can make cigarette stubs considerable as a recycled product that reduces the environment's waste. The results obtained by plants treated with biopesticides effectively resist pest attacks and support plants to naturally develop antibodies. The score of Intensity Attack (IS) from Terminalia cattapa plant applied by the biopesticides for 10 days observation results in the amount of 3.953%, with a total of 34 normal leaves and a total of 12 broken leaves. The other result of the Terminalia cattapa applied with chemical pesticides gives 12.31% of intensity attack and 12.18% of intensity attack without any treatment. This research concluded that tobacco could inhibit the attack pest of the Terminalia cattapa plant.